2002
DOI: 10.1002/mrc.1099
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed field gradient NMR investigation of solubilization equilibria in amino acid and dipeptide terminated micellar and polymeric surfactant solutions

Abstract: Pulsed field gradient NMR spectroscopy was used to investigate the association of toluene, chlorobenzene and benzyl alcohol with amino acid and dipeptide terminated polymerized surfactants (PS). The diffusion coefficient for each probe was measured in the presence and absence of the polymers and the mole fraction of bound probe molecules, f b , was calculated. For all solutions investigated, the probes associated more strongly with unpolymerized surfactant micelles than with corresponding PS. For example, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A major difference between the micelles of conventional surfactant monomers and polymeric surfactants is that there usually is a covalent linkage in individual polymeric surfactant molecules within the hydrophobic core that does not allow dynamic exchange of monomers between free solution and the micellar pseudo-phase. This confers rigidity and stability to the polymeric micelles [6]. The diameter of polymeric micelle ranges from 10 to 100 nm.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…A major difference between the micelles of conventional surfactant monomers and polymeric surfactants is that there usually is a covalent linkage in individual polymeric surfactant molecules within the hydrophobic core that does not allow dynamic exchange of monomers between free solution and the micellar pseudo-phase. This confers rigidity and stability to the polymeric micelles [6]. The diameter of polymeric micelle ranges from 10 to 100 nm.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…The PFG-NMR diffusion method for determining association constants becomes less accurate as the binding constants become large because the denominator in Eqn (4) contains the term (1 f b ). 23,24,33 Therefore, small changes in f b can produce large changes in the association constant when f b approaches one. If we instead compare the f b values for Leu-enkephalin-Arg and Leu-enkephalin-Lys, the respective mole fractions of 0.986 and 0.988 are nearly equal, suggesting that the affinity of these two peptides for the micelles is similar.…”
Section: Resultsmentioning
confidence: 98%
“…This comparison suggests that in both the poly(SULV) and poly(SUVL) MM structures, more of the surfactant chain area is accessible to water molecules than in a corresponding SDS micelle. It is also interesting to note that NMR diffusion studies have shown that small non-polar probe molecules solubilize in the interior of SDS and unpolymerized amino acid-based surfactant micelles to a much greater degree than into the corresponding MM [27). For example, the mole fraction of toluene molecules solubilzed into unpolymerized micelles formed by the amino acid-based surfactants sodium undecyl-(L,L)-valine and sodium undecyl-(L,L)-valine-valine were found to be 0.88 and 0.90 respectively.…”
Section: Resultsmentioning
confidence: 99%